Enhancing effect of cystamine in its amides with betulinic acid as antimicrobial and antitumor agent in vitro - Bildziukevich, Uladzimir; Rárová, Lucie; Janovská, Lucie; Šaman, David; Wimmer, Zdeněk (Steroids, 2019)
Amides of betulinic acid with cystamine were synthesized to investigate their antimicrobial and antitumor activity, and their influence on the cell cycle and cell apoptosis. The former target amide (6) displayed cytotoxicity in CEM cell line after 72 h of treatment (IC50 = 3.0 ± 0.7 μM; TI = 20), and induced apoptosis by caspase-3/7 activation in CEM cells. The latter target amide (9) displayed antimicrobial activity against Streptococcus mutans (MIC 3.125 μM; MBC 3.125 μM) and Bacillus cereus (MIC 25 μM; MBC 25 μM). The achieved results demonstrate enhancing of their biological activity over that of the parent compounds. However, two intermediate compounds (2 and 7) displayed either considerable cytotoxicity (2; 7.5 ± 0.8 μM; TI = 10, against G361) or antimicrobial activity (7; both against Actinomyces odontolycus and Clostridium perfrigens with MIC 12.5 µM and MBC 12.5 µM). The experimental data were compared with the in silico calculated physico-chemical and ADME parameters of the target compounds, including successful intermediates.
Keywords: Betulinic Acid; Microbial Sensitivity Tests; molekulární konformace; Pentacyclic Triterpenes; Molecular Conformation; cystamin; Drug Screening Assays, Antitumor; Humans; Cytotoxicity; Streptococcus mutans; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Dose-Response Relationship, Drug; Antineoplastic Agents; mikrobiální testy citlivosti; pentacyklické triterpeny; Triterpenes; Amides; lidé; Betulinic acid; antibakteriální látky; proliferace buněk; Cells, Cultured; Clostridium; Actinomyces; apoptóza; Antimicrobial activity; Cystamine; kyselina betulinová; Anti-Bacterial Agents; triterpeny; kultivované buňky; Cell Proliferation; screeningové testy protinádorových léčiv; protinádorové látky; vztah mezi dávkou a účinkem léčiva; Bacillus cereus; amidy; Apoptosis